2002
DOI: 10.1002/em.10085
|View full text |Cite
|
Sign up to set email alerts
|

Dietary folate deficiency enhances induction of micronuclei by arsenic in mice†

Abstract: Folate deficiency increases background levels of DNA damage and can enhance the genotoxicity of chemical agents. Arsenic, a known human carcinogen present in drinking water supplies around the world, induces chromosomal and DNA damage. The effect of dietary folate deficiency on arsenic genotoxicity was evaluated using a mouse peripheral blood micronucleus (MN) assay. In duplicate experiments, male C57Bl/6J mice were fed folate-deficient or folate-sufficient diets for 7 weeks. During week 7, mice on each diet w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 45 publications
(55 reference statements)
3
21
2
Order By: Relevance
“…As shown in the results, a low folate status increased susceptibility to benzene-induced chromosomal damage. It has been shown that feeding of a folate deficient diet alone for 7 wk increased slight but significant chromosomal damage in bone marrow (9,10). In this study, we could not replicate the same findings even though we evaluated the damage using the same MN method.…”
contrasting
confidence: 80%
“…As shown in the results, a low folate status increased susceptibility to benzene-induced chromosomal damage. It has been shown that feeding of a folate deficient diet alone for 7 wk increased slight but significant chromosomal damage in bone marrow (9,10). In this study, we could not replicate the same findings even though we evaluated the damage using the same MN method.…”
contrasting
confidence: 80%
“…Rat and rabbit Mukherjee et al (2003Mukherjee et al ( , 2004 Cancer Liver, adrenal, ovarian and lung tumors Mouse Cui et al (2006); Waalkes et al (2003) Genotoxicity Somatic mutations and mitotic recombination, chromosomal aberrations (bone marrow cells), Drosophila melanogaster, rat and Das et al (1993); Datta et al (1986);McDorman et al (2002); Poddar et al (2000); Ramos-Morales and Rodríguez-Arnaiz (1995) (continued on next page) (Geens et al, 2010;Hofer et al, 2010). Moreover, breeding parameters such as clutch size, length of the incubation period or hatching and fledging success are evaluated to study the effects of As and metals in breeding performance.…”
Section: Renal Effectsmentioning
confidence: 97%
“…Folate is a B vitamin that normally functions in DNA methylation, synthesis and repair (Choi and Mason, 2000). A number of experimental studies in rodents, and in human and rodent cell culture systems, have shown that folate deficiency can enhance the genotoxicities of arsenic and other chemicals (MacGregor et al, 1990;Branda et al, 2001;McDorman et al, 2002). Folate deficiency and other methyl deficient diets, in the absence of any known carcinogen exposure, have been associated with increased risks of cancer of the colorectum, esophagus, cervix, lung, brain, pancreas, breast and liver (Mikol et al, 1983;Ghoshal and Farber, 1984;Choi and Mason, 2000).…”
Section: Introductionmentioning
confidence: 99%